PENGARUH KOMUNIUKASI PEMASARAN DAN PROMOSI HARGA TERHADAP VARIABEL EKUITAS MEREK AIR MINUM KEMASAN DANONE-AQUA - ESAU MANDANG, ADITYA ANDIKA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The purpose of this study was to find out the impact of marketing communication and price promotion on brand equity dimension on Danone-Aqua mineral water in Surabaya. The populations of this study are all of Danone-Aqua mineral water customers in Surabaya. The sampling technique used was non probability sampling, with the criteria of at least 17 years of age because at that age are considered adults and can make decisions. This research was using Structural Equation Model (SEM) as the analysis technique. Based on the results obtained that the perceived advertising spending have a positive effect on perceived quality, perceived advertising spending have a positive effect on brand awareness, perceived advertising spending have a positive effect on brand image, perceived advertising spending have a positive effect on brand loyalty, price promotion not have a negative effect on perceived quality, price promotion not have a negative effect on brand image, brand awareness have a positive effect on brand image.